Dilema Keamanan dan Respons Kolektif ASEAN Terhadap Sengketa Laut Cina Selatan - Yoga Suharman (Intermestic: Journal of International Studies, 2019)
The article aims to explain two dimensions of political-security in the South China Sea. First, the collective response of ASEAN in an effort to maintain security stability in the South China Sea by looking the belief system of interested parties. Second, the configuration of extra-regional power within the sphere of influence in the disputed area. This article uses perception theory and the concept of security dilemma. The data and information of this article obtained from secondary sources which are interpreted to produce descriptive analytical explanations. The article indicates that some of the South China Sea interested parties which are ASEAN members has different belief systems in perceiving security threats that are increasingly complicated by the configuration of extra-regional power.